Ultrasound surveillance for radiation-induced thyroid carcinoma in adult survivors of childhood cancer. (March 2016) - Brignardello, Enrico; Felicetti, Francesco; Castiglione, Anna; Gallo, Marco; Maletta, Francesca; Isolato, Giuseppe; Biasin, Eleonora; Fagioli, Franca; Corrias, Andrea; Palestini, Nicola
Abstract: Introduction: The optimal surveillance strategy to screen for thyroid carcinoma childhood cancer survivors (CCS) at increased risk is still debated. In our clinical practice, beside neck palpation we routinely perform thyroid ultrasound (US). Here we describe the results obtained using this approach. Methods: We considered all CCS referred to our long term clinic from November 2001 to September 2014. One hundred and ninety-seven patients who had received radiation therapy involving the thyroid gland underwent US surveillance. Thyroid US started 5 years after radiotherapy and repeated every 3 years, if negative. Results: Among 197 CCS previously irradiated to the thyroid gland, 74 patients (37.5%) developed thyroid nodules, and fine-needle aspiration was performed in 35. In 11 patients the cytological examination was suspicious or diagnostic for malignancy (TIR 4/5), whereas a follicular lesion was diagnosed in nine. Patients with TIR 4/5 cytology were operated and in all cases thyroid cancer diagnosis was confirmed. The nine patients with TIR 3 cytology also underwent surgery and a carcinoma was diagnosed in three of them. Prevalence of thyroid cancer was 7.1%. Tumour size ranged between 4 and 25 mm, but six (43%) were classified T3 because of extra-thyroidal extension. Six patients had nodal metastases; in eight patients the tumour was multifocal. At the time of the study all patients are disease free, without evidence of surgery complications. Conclusion: Applying our US surveillance protocol, the prevalence of radiation-induced thyroid cancer is high. Histological features of the thyroid cancers diagnosed in our cohort suggest that most of them were clinically relevant tumours. Highlights: When screened with thyroid ultrasound (US), the incidence of thyroid cancer in irradiated childhood cancer survivors (CCS) is high (7.1%). Clinical/histological features suggest that diagnosed tumours are clinically relevant. In CCS irradiated to the thyroid gland US surveillance could be worthwhile.